Islamic Religious Education Teacher Strategies in Implementing Multicultural Values in Darurrahmah Sepadan Junior High School - Dumilah, Reno; Syahputri, Yuliana; Hanum, Azizah (JASNA : Journal For Aswaja Studies, 2025)
This study aims to investigate the strategies of Islamic Religious Education teachers in instilling multicultural values at SMP Swasta Darurrahmah Sepadan. The focus of the study covers three main aspects: the values of pluralism, humanity, and democracy applied in this school, the planning process and implementation of strategies by teachers, and the supporting and inhibiting factors in the integration of these values. This study uses a qualitative descriptive approach with data collection methods through observation and interviews. Data analysis is done through data reduction, data presentation, and conclusion to verify the findings. The study results indicate that the multicultural values integrated into religious education in class VIII C of SMP Swasta Darurrahmah Sepadan include tolerance, cooperation, mutual respect, justice, freedom, equality, and brotherhood. The implications of this study confirm that effective strategies for instilling multicultural values can be a model for other schools in building an inclusive and harmonious educational environment.